Newborn Screening by Tandem Mass Spectrometry: Ethical and Social Issues - Avard, Denise (Can J Public Health, 2007)
Emerging technologies like Tandem Mass Spectrometry (TMS) enable multiple tests on a single blood sample and allow the expansion of Newborn Screening (NBS) to include various metabolic diseases. Introducing TMS for NBS raises important social and ethical questions: what are the criteria for adding disorders to screening panels? What evidence justifies expansion of screening? How can equity in NBS access and standards be ensured? How can policy standards be set, given the multiplicity of stakeholders? To address emerging issues, policy-makers, patient advocates, clinicians and researchers had a workshop during the 2005 Garrod Symposium. The participants received a summary of the discussion and understood the workshop’s goal was to provide a basis for further discussion. This article contributes to this ongoing discussion. Several proposed recommendations assert the centrality of including social and ethical issues in the assessment of whether or not to introduce TMS. The article outlines five key recommendations for advancing the NBS agenda: national public health leadership; transparency; increased national consistency in NBS strategy, including minimum standards; collaboration between the federal and provincial/territorial governments and diverse stakeholders; and supporting research and/or programs based on effectiveness, which integrate ethical and social issues into assessment.